Effect of Respiration Training-Assisted Western Medicine Therapy on Activity Tolerance, Pulmonary Function, and Quality of Life of Chronic Obstructive Pulmonary Disease Patients in the Stable Phase. (30th March 2022) - Tong, Yaqi; Cui, Jia; Chai, Di
Abstract : Objective . To explore the effect of respiration training-assisted western medicine therapy on activity tolerance, pulmonary function, and quality of life (QOL) of chronic obstructive pulmonary disease (COPD) patients in the stable phase. Methods . The medical data of 90 COPD patients in the stable phase treated in the respiratory medicine of our hospital (November 2020–November 2021) were chosen for the retrospective analysis, and the patients were split into group A ( n = 45, respiration training-assisted western medicine therapy) and group B ( n = 45, western medicine therapy) according to the clinical reception order, so as to record and compare the activity tolerance, lung function, and QOL between the groups after intervention. Results . Compared with group B after intervention, group A showed greatly longer mean 6-min walking distance, significantly lower St. George's Respiratory Questionnaire (SGRQ) score, significantly higher specific airway conductance (sGAW) and level values of various lung function indicators, and significantly lower level values of airway resistance (RAW) and specific airway resistance (sRAW) (p all<0.001); the total effective rate was significantly higher in group A (p < 0.05). Conclusion . Respiration training-assisted western medicine therapy is a dependable way to improve the activity tolerance of COPD patients in the stable phase, and such strategy largely improves patients' lung function and QOL. Deeper studies will be helpful to establish a preferable solution for such patients.